Synthesis and biological evaluation of chalcone, dihydrochalcone, and 1, 3-diarylpropane analogs as anti-inflammatory agents. Issue 7 (1st April 2017) - Vijaya Bhaskar Reddy, Mopur; Hung, Hsin-Yi; Kuo, Ping-Chung; Huang, Guan-Jhong; Chan, Yu-Yi; Huang, Shiow-Chyn; Wu, Shwu-Jen; Morris-Natschke, Susan L.; Lee, Kuo-Hsiung; Wu, Tian-Shung
Graphical abstract: Abstract: Twenty-one chalcones were prepared via aldol condensation and subsequent reduction of these compound led to the corresponding dihydrochalcone and 1, 3-diphenylpropane derivatives. The synthetic products were examined for their effects on NO inhibition in LPS-activated mouse peritoneal macrophages. Among the tested compounds, a 1, 3-diarylpropane analog, 2-(3-(3, 4-dimethoxyphenyl)propyl)-5-methoxyphenol (3p ), displayed the most significant inhibitory effects against NO production. To investigate the mechanism of action, the effects of3p on i NOS and COX-2 protein expression were studied by immunoblot. The results concluded that3p is capable of inhibiting i NOS expression in LPS-induced RAW264.7 cells via attenuation of NF-κB signaling by ERK, p38, and JNK.